The potential climatic range of spotted lanternfly may be broader than previously predicted - Keena, Melody A.; Hamilton, George; Kreitman, Devin (Frontiers in Insect Science, 2023)
Spotted lanternfly (Lycorma delicatula White) is an invasive planthopper that was introduced to the United States from Asia and readily spreads via human aided means. Three geographically separated populations in the United States (NJ, PA, and WV) were collected and used to assess the effects of fluctuating thermal regimes that included temperatures above or below the upper (Tmax) and lower (Tmin) developmental thresholds, respectively, on nymphal survival and development, and to determine if there was within- and among-population variation in hatch timing and temperature responses of nymphs. Nymphs exposed to temperatures > Tmax and